المساهمة في دراسة تأثير المستخلص الميثانولي لنبات النتين على حافرة الطماطم وعلى مورفولوجيا و فيزيولوجيا نبات الطماطم - باحدي, خديجة; بكاكرة, بشيرة (Université of eloued جامعة الوادي, 2019)
The purpose of this study was to test the methanolic extract of leaves and seeds Cléom arabica on some properties of Lycopersicon esculentum chibil variety by spraying for 12 weeks. Three consecutive concentrations of each extract were tested for 0.5 mg / ml, 0.75 mg / ml and 1 mg / ml. The insect was treated by direct spraying and the observation was followed at two intervals (24-48 hours). Toxic effect on Tuta absoluta compared to Ampligo® 150 ZC, especially at concentrations of 1 mg / ml, 0.75 mg / ml, with death rate at Fc1 = 100% and Gc1 = 80%. Improvement of some properties of tomatoes treated with plant extracts compared to the control where these extracts worked as fertilizers, which led to improved growth.
Biologie et Valorisation des Plantes
Keywords: المستخلص الميثانولي ، نبات التين ، نبات الطماطم; methanolic extract. Tuta absoluta . Tomato plant. Biological combat fertilizers. improved growth